Short-term exposure to fine particulate matter and its constituents may affect renal function via oxidative stress: A longitudinal panel study. (April 2022) - Peng, Shouxin; Lu, Tianjun; Liu, Yisi; Li, Zhaoyuan; Liu, Feifei; Sun, Jinhui; Chen, Meijin; Wang, Huaiji; Xiang, Hao
Abstract: Exposure to fine particulate matter (PM2. 5 ) has been reported to increase the risks of chronic kidney disease. However, limited research has assessed the effect of PM2.5 and its constituents on renal function, and the underlying mechanism has not been well characterized. We aimed to evaluate the association of PM2.5 and its constituents with kidney indicators and to explore the roles of systematic oxidative stress and inflammation in the association. We conducted a longitudinal panel study among 35 healthy adults before-, intra- and after-the 2019 Wuhan Military World Games. We repeatedly measured 6 renal function parameters and 5 circulating biomarkers of oxidative stress and inflammation at 6 rounds of follow-ups. We monitored hourly personal PM2.5 concentrations with 3 consecutive days and measured 10 metals (metalloids) and 16 polycyclic aromatic hydrocarbons (PAHs) components. The linear mixed-effect models were applied to examine the association between PM2.5 and renal function parameters, and the mediation analysis was performed to explore potential bio-pathways. PM2.5 concentrations across Wuhan showed a slight decrease during the Military Games. We observed significant associations between elevated blood urea nitrogen (BUN) levels and PM2.5 and its several metals and PAHs components. For an interquartile range (IQR) increase of PM2.5, BUN increased 0.42 mmol/L (95% CI: 0.14 to 0.69). On average, an IQR higher of lead (Pb), cadmium (Cd), arsenic (As), selenium (Se), thallium (Tl) and Indeno (1, 2, 3-cd) pyrene (IPY) were associated with 0.90, 0.65, 0.29, 0.27, 0.26 and 0.90 mmol/L increment of BUN, respectively. Moreover, superoxide dismutase was positively associated with PM2.5 and mediated 18.24% association. Our research indicated that exposure to PM2.5 might affect renal function by activating oxidative stress pathways, in which the constituents of Pb, Cd, As, Se, Tl and IPY might contribute to the associations. Graphical abstract: Image 1 Highlights: Short-term exposure to PM2.5 may affect renal function among healthy adults. Ad, Pb, As, Se, Tl and IPY in PM2.5 might contribute to the association. Oxidative stress might be a bio-pathway between PM2.5 and renal function.